Comprehensive investigation on active-passive hybrid isolation and tunable dynamic vibration absorption - Wang, Fei; Weng, Zhenping; He, Lin (Singapore : Springer Nature, 2019)
This book discusses efforts to control the low-frequency vibration transmission of typical power equipment and pipeline systems of ships, exploring the use of active and passive hybrid vibration isolation and adjustable dynamic vibration absorption technologies. It also proposes an adaptive feed-forward control strategy and studies a distributed feed-forward control hardware system. In addition, the book presents a three-way dynamic vibration absorption theory used to design a pipeline-system adjustable dynamic vibration absorber, which offers a number of advantages, such as compact structure, easy assembly and disassembly, low power consumption, excellent vibration control effect and wide frequency band adjustable ability, etc. This book is a valuable resource for researchers and engineers in the fields of noise and vibration control, active control systems, active vibration isolation and adaptive dynamic vibration absorption.
Keywords: Vibration (Marine engineering)